2019
DOI: 10.1080/01431161.2019.1673917
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the annual dynamics of cultivated land in typical area of the Middle-lower Yangtze plain using long time-series of Landsat images based on Google Earth Engine

Abstract: Cultivated land in Middle-lower Yangtze Plain has been greatly reduced over the last few decades due to rapid urban expansion and massive urban construction. Accurate and timely monitoring of cultivated land changes has significant for regional food security and the impact of national land policy on cultivated land dynamics. However, generating high-resolution spatial-temporal records of cultivated land dynamics in complex areas remains difficult due to the limitations of computing resources and the diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Studies have shown that LCLUC has a certain impact on climate and regional precipitation, and many scholars have carried out related studies in this regard [1][2][3]10,12]. Some scholars have analyzed the influence of cropland, forest, and urban change on precipitation in specific regions [13,14,17,19,20]. However, there have been no reports on the spatialtemporal effects of LCLUC on precipitation in the GBA, especially construction land and cropland change on regional precipitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that LCLUC has a certain impact on climate and regional precipitation, and many scholars have carried out related studies in this regard [1][2][3]10,12]. Some scholars have analyzed the influence of cropland, forest, and urban change on precipitation in specific regions [13,14,17,19,20]. However, there have been no reports on the spatialtemporal effects of LCLUC on precipitation in the GBA, especially construction land and cropland change on regional precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies focused on the impact of urbanization on urban precipitation and the impact of forest or farmland on regional precipitation, while there were few studies on the underlying surface structure and the change of regional water resources in the water-air cycle [17][18][19]. It was found that the change of urban construction land has an important influence on the change of regional precipitation, vegetation, and land surface temperature, but it failed to quantitatively express the influence among them [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, Google Earth Engine (GEE) provides an outstanding cloud computing platform with open access to a variety of EO data. Thanks to the potential of big data processing of these platforms, researchers have completed extensive studies at greater extent, for example, on urban change monitoring 22 , cultivated land mapping 23 , and forest disturbance detection 24 . Multi-category land cover products were also produced such as a 13-category land cover map of South-east Asia covering 11 nations 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The training samples used by the random forest classifier are extracted from Google Earth high-resolution images (1 m × 1 m) by visual inspection, 500 for each year. The primary variables adopted in the classification include spectral bands, normalized difference vegetation index, grey level co-occurrence matrix with respect to imagery texture and topographic variables (e.g., slope and aspect; see [22] for technical details).…”
Section: Detection Of Urban Expansion Using Satellite Imagesmentioning
confidence: 99%